Pengaruh Fraud Hexagon Theory Terhadap Academic Fraud Mahasiswa Akuntansi - Anggrezola, Nathasya; Setiawan, Mia Angelina (Universitas Negeri Padang, 2026)
The purpose of this study was to determine how Fraud Hexagon Theory affects Academic Fraud of accounting students. There are 283 people were used to represent the entire population of accounting students from Universitas Negeri Padang, Universitas Andalas, Universitas Bung Hatta, Universitas Putra Indonesia